The Influence of Principal Communication and Principal's Academic Supervision on Teacher Performance in South Pemulutan - Zalli Zalli; Pahlawan Pahlawan (International Journal of Educational Development, 2025)
This study aims to find out and analyze: (1) The relationship between the principal's communication and teacher performance; (2) The relationship between the principal's academic supervision and teacher performance; and (3) The relationship between the principal's communication and the principal's academic supervision on teacher performance. This study is a quantitative research with a partial correlation method. This research was conducted at SD Negeri Pemulutan Selatan which consisted of 38 teachers and 5 principals so that the total number of respondents was 43. The data collection technique uses questionnaires and documentation. The validation test uses construct validity while the reality test uses Cronbachh's Alpha. The prerequisite test for analysis uses normality test, homogeneity test, and linearity test, and the data is analyzed using simple regression and multiple regression techniques. The results of the study showed that: (1) there was a positive and significant relationship between the principal's communication and teacher performance with a correlation value of 0.923 with a relationship percentage of 85% while 15% was determined by other factors that were not mentioned. (2) There was a positive and significant relationship between the principal's academic supervision and teacher performance with a correlation value of 0.946 with a relationship percentage of 89%, while 11% was determined by other factors that were not mentioned. (3) There was a positive and significant relationship between the principal's communication and the principal's academic supervision on teacher performance with a correlation value of 0.953 with a relationship percentage of 91%, while 9% was determined by other factors not mentioned in this study.